Attention-deficit hyperactivity disorder : a clinical workbook - Barkley, Russell A.; Murphy, Kevin R. (New York ; London : Guilford, 1998)
ADHD fact sheet Forms for use with children and adolescents
Instructions for child and adolescent forms
General instructions for completing the questionnaires
Developmental and medical history
How to prepare for your child's evaluation
Clinical interview--Parent report form
Disruptive Behavior Rating Scale--Parent form
Disruptive Behavior Rating Scale--Teacher form
Home Situations Questionnaire
School Situations Questionnaire
Issues Checklist for parents and teenagers
Using a daily school behavior report card
Forms for the evaluation of adults
Instructions for adult forms
Developmental history
Employment history
Health history
Social history
Current Symptoms Scale--Self-report form
Childhood Symptoms Scale--Self-report form
Current Symptoms Scale--Other report form
Childhood Symptoms Scale--Other report form
Childhood School Performance Scale--Other report form
Work Performance Rating Scale--Self-report form
Adult interview
Forms for use during medication treatment
Physician's checklist for parents
Follow-up information
Side effects rating scale
Keywords: hiperaktivnost; psihodijagnostika